Voltage And Frequency Control Of Microgrid System With Demand Response - Alias , Khamis; Mohd Ruddin, Ab Ghani; Gan, Chin Kim; Muhammad Nizam , Kamarudin (United Kingdom Simulation Society, 2016)
This paper describe the operation of Microgrid system with integrated photovoltaic, fuel cell and battery bank. Photovoltaic represents variable resources whereas fuel cell represents dispatch-able resources. These sources are coupled to grid through power electronic converter. The inverters are controlled by decoupled control method. The frequency and voltage inside Microgrid is controlled by performing fast demand respond. The proof of concept for this study is performed in MATLAB with SIMPOWERSYSTEM toolbox. The simulation results show that fast demand respond is capable in controlling the voltage and frequency of the interconnected Microgrid system.